2017
DOI: 10.3390/ijerph14111431
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Violence against Children in South Africa

Abstract: The purpose of this study was to estimate the economic burden of violence against children in South Africa. We assembled summative estimates of lifetime prevalence, calculated the magnitude of associations with negative outcomes, and thereby estimated the economic burden of violence against children. According to our calculations, 2.3 million and 84,287 disability-adjusted life-years (DALYs) lost in South Africa in 2015 were attributable to nonfatal and fatal violence against children, respectively. The estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 32 publications
1
39
0
1
Order By: Relevance
“…Based on these prevalence data, the economic cost of sexual, physical and emotional violence perpetrated against children in SA, and neglect of children -including disabilityadjusted life-years lost due to death and ill health, reduced earnings and welfare costs -is estimated as being ZAR196 billion, or 4.9% of SA's gross domestic product. [12] Objective Taking advantage of a large corpus of longitudinal data collected in the Birth to Twenty Plus (Bt20+) cohort, to give a perspective of exposure to and experience of violence, as well as perpetration of violence, across the time span of childhood, reported contemporaneously by several informants from infancy to young adulthood. These data overcome several limitations of retrospectively recalled information collected from one person at one point in time.…”
Section: Researchmentioning
confidence: 99%
“…Based on these prevalence data, the economic cost of sexual, physical and emotional violence perpetrated against children in SA, and neglect of children -including disabilityadjusted life-years lost due to death and ill health, reduced earnings and welfare costs -is estimated as being ZAR196 billion, or 4.9% of SA's gross domestic product. [12] Objective Taking advantage of a large corpus of longitudinal data collected in the Birth to Twenty Plus (Bt20+) cohort, to give a perspective of exposure to and experience of violence, as well as perpetration of violence, across the time span of childhood, reported contemporaneously by several informants from infancy to young adulthood. These data overcome several limitations of retrospectively recalled information collected from one person at one point in time.…”
Section: Researchmentioning
confidence: 99%
“…Multiple studies have found that more than 50% of Cambodian children are physically punished by their parents or adult relatives (Fordham, ; Miles & Thomas, ; Miles & Varin, ; Ministry of Women's Affairs, UNICEF Cambodia, Centers for Disease Control and Prevention, ; Save the Children Sweden, ). Fang () reported that in Cambodia, roughly 22% of females and 26% of males aged 13–24 had been abused by a parent, caregiver, or adult relative and that approximately 5% of them reported some form of sexual abuse prior to age 18. The United States (US) Centers for Disease Control and Prevention () similarly reported that the prevalence of any form of childhood sexual violence in Cambodia was 4.4% in females and 5.6% in males.…”
Section: Introductionmentioning
confidence: 99%
“…The United States (US) Centers for Disease Control and Prevention () similarly reported that the prevalence of any form of childhood sexual violence in Cambodia was 4.4% in females and 5.6% in males. Meanwhile, Fang () noted that 25% of Cambodian children aged 13–24 had been emotionally abused and reported gender differences in terms of child abuse and health outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisa realizada na África do Sul avaliou que os gastos com cuidados e proteção infantil, nos anos de 2015 e 2016, atingiu 124 milhões de dólares, sendo que, muitos dos custos estão diretamente relacionados à problemática. 4 No Brasil, os dados do Sistema de Informação de Agravos de Notificação (SINAN), no ano de 2014 destacaram que foram notificados 38.248 casos de violência contra a criança, sendo que, parte das agressões ocorreram no âmbito doméstico, tendo como principais agressores os pais, seguidos de pessoas mais próximas como padrastos e madrastas. 5 Nessa perspectiva, a violência contra a criança pode ocorrer das seguintes formas: física, psicológica, sexual e negligência, sendo que cada uma delas pode vir acompanhada por outra forma.…”
Section: Introductionunclassified